Affinity and selectivity of plant proteins for red wine components relevant to color and aroma traits. (1st August 2018) - Granato, Tiziana Mariarita; Ferranti, Pasquale; Iametti, Stefania; Bonomi, Francesco
Highlights: Plant proteins are as effective as gelatin in fining red wine. Individual plant proteins have a different impact on specific wine traits. Protein hydrolysates behaved differently from the intact proteins. Impact of fining decreased with wine ageing. Abstract: The effects of fining with various plant proteins were assessed on Aglianico red wine, using both the young wine and wine aged for twelve and twenty-four months, and including wine unfined or fined with gelatin as controls. Color traits and fining efficiency were considered, along with the content of various types of phenolics and of aroma-related compounds of either varietal or fermentative origin. All agents had comparable fining efficiency, although with distinct kinetics, and had similar effects on wine color. Individual plant proteins and enzymatic hydrolyzates differed in their ability to interact with some anthocyanins, with specific proanthocyanidins complexes, and with some aroma components of fermentative origin. Changes in varietal aroma components upon fining were very limited or absent. Effects of all the fining agents tested in this study on the anthocyanidin components were most noticeable in young red wine, and decreased markedly with increasing wine ageing.